Prior family communication and consent to organ donation: using intensive care physicians’ perception to model decision processes - Peter J. Schulz; Ann van Ackere; Uwe Hartung; Anke Dunkel (Journal of Public Health Research, 2012)
Generally, the Swiss hold favourable attitudes to organ donation, but only few carry a donor card. If no card is found on a potential donor, families have to be approached about donation. The aim of this paper is to model the role that some family communication factors play in the family decision to consent or not to organ donation by a brain dead relative. Information was gathered in face-to-face interviews, using a questionnaire and recording open answers and comments. Eight heads of intensive care units (ICU) of Swiss hospitals and one representative from Swisstransplant were interviewed. Questions asked respondents to estimate the prevalence and effect of communication factors in families facing a decision to consent to donation. Answers were averaged for modelling purposes. Modelling also relies on a previous representative population survey for cross-validation. The family of the deceased person is almost always approached about donation. Physicians perceive that prior thinking and favourable predisposition to donation are correlated and that the relatives’ predisposition is the most important factor for the consent to donation, up to the point that a negative predisposition may override an acknowledged wish of the deceased to donate. Donor cards may trigger family communication and ease the physicians’ approach to family about donation. Campaigns should encourage donate-willing people to talk to their families about it, make people think about organ donation and try to change unfavourable predispositions.